2014
DOI: 10.3389/fpls.2014.00088
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the functional virulent genome of the coffee leaf rust pathogen Hemileia vastatrix with an emphasis on early stages of infection

Abstract: Hemileia vastatrix is the causal agent of coffee leaf rust, the most important disease of coffee Arabica. In this work, a 454-pyrosequencing transcriptome analysis of H. vastatrix germinating urediniospores (gU) and appressoria (Ap) was performed and compared to previously published in planta haustoria-rich (H) data. A total of 9234 transcripts were identified and annotated. Ca. 50% of these transcripts showed no significant homology to international databases. Only 784 sequences were shared by the three condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 79 publications
4
41
0
Order By: Relevance
“…The S H 1 gene has not yet been cloned and thus, conventional transient coexpression assays in other plant species, such as Nicotiana benthamiana , are not possible at the moment. Notably, H. vastatrix isolate 178a (race XIV), which is also avirulent on S H 1 plants, carries the same allele of HvEC‐016 as that of isolate Hv‐01 (race II) (Fernandez et al ., ; Talhinhas et al ., ). Also, consistent with the expression profile observed in our study, HvEC‐016 was identified in all three libraries of isolate 178a (interaction, appressoria and germinating urediniospores) screened by these authors.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The S H 1 gene has not yet been cloned and thus, conventional transient coexpression assays in other plant species, such as Nicotiana benthamiana , are not possible at the moment. Notably, H. vastatrix isolate 178a (race XIV), which is also avirulent on S H 1 plants, carries the same allele of HvEC‐016 as that of isolate Hv‐01 (race II) (Fernandez et al ., ; Talhinhas et al ., ). Also, consistent with the expression profile observed in our study, HvEC‐016 was identified in all three libraries of isolate 178a (interaction, appressoria and germinating urediniospores) screened by these authors.…”
Section: Discussionmentioning
confidence: 98%
“…Here we report a total of 94 Hemileia ‐specific candidate effector genes, referred to as HvEC s, of which 14 have not been reported previously. We provide for 34 earlier partial effectors full‐length sequences, and confirm 46 effector sequences already published (Fernandez et al ., ; Cristancho et al ., ; Talhinhas et al ., ). We identified genes encoding proteins with significant similarity to the previously reported RTP1 (Kemen et al ., ; Vieira et al ., ; Pretsch et al ., ) and HESP proteins (Dodds et al ., ; Barrett et al ., ) in the H. vastatrix secretome, providing validation for our prediction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dikaryotic aeciospores and urediniospores enter the host leaf through openings in the stomata, after appressorium differentiation (Voegele et al, 2009). Several transcriptomic analyses of appressoria formation of urediniospores led to identification of the genes responsible for metabolism and regulation of the cell division cycle, indicating that this structure plays an active role in the penetration process (Hu et al, 2007;Stone et al, 2012;Talhinhas et al, 2014). Urediniospores from the soybean rust fungus directly penetrate their host through the epidermis, in a similar manner to basidiospores of heteroecious fungi, and form an appressorium with a high cell turgor pressure of 5.13 MPa (Loehrer et al, 2014a), which correlates with what has been observed in other fungal plant pathogens (Ryder & Talbot, 2015).…”
Section: Early Stages Of Infection: Host Penetration and Haustorium Fmentioning
confidence: 99%
“…Hundreds of candidate effectors have been identified in H. vastatrix by genomic and transcriptomic approaches (Fernandez et al, 2012;Cristancho et al, 2014;Talhinhas et al, 2014). Similar to effectoromic screens conducted in P. graminis f. sp.…”
Section: Effectoromics Of the Coffee Rust Fungus H Vastatrixmentioning
confidence: 99%